2015
DOI: 10.1039/c5ra01814e
|View full text |Cite
|
Sign up to set email alerts
|

Beta-lactoglobulin-based encapsulating systems as emerging bioavailability enhancers for nutraceuticals: a review

Abstract: Encapsulating systems prepared with beta-lactoglobulin, the major component of whey protein, may serve as versatile bioavailability enhancers for poorly absorbed nutraceuticals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
46
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(49 citation statements)
references
References 107 publications
(110 reference statements)
3
46
0
Order By: Relevance
“…The binding affinity of these new calix[4]arenes toward β‐lactoglobulin (BLG) as a model protein was investigated by using fluorescence spectrophotometric methods. We used BLG as a model protein because of its natural abundance, high stability, and numerous physiological and pharmacological functions . Because these designed molecules have multifunctional structures, associative, non‐covalent binding forces, such as hydrogen bonding, hydrophobic interaction, and van der Waals interactions, are expected.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The binding affinity of these new calix[4]arenes toward β‐lactoglobulin (BLG) as a model protein was investigated by using fluorescence spectrophotometric methods. We used BLG as a model protein because of its natural abundance, high stability, and numerous physiological and pharmacological functions . Because these designed molecules have multifunctional structures, associative, non‐covalent binding forces, such as hydrogen bonding, hydrophobic interaction, and van der Waals interactions, are expected.…”
Section: Introductionmentioning
confidence: 99%
“…We used BLG as a model protein because of its natural abundance, high stability, and numerous physiological and pharmacological functions. [28] Because these designed molecules have multifunctional structures, associative, non-covalent binding forces, such as hydrogen bonding, hydrophobic interaction, and van der Waals interactions, are expected. We believe that six amide groups are necessary for the formation of hydrogen bonding between ligand and protein.…”
mentioning
confidence: 99%
“…The chemical and enzymatic hydrolyses, the acylation [21], cationization [21,78] and Maillard reactions [12,19,77] are the best chemical treatments to improve their functionality [12,43]. For instance, Nesterenko et al [46] studied native and modified soybean and sunflower seed proteins to encapsulate α-tocopherol by spray drying.…”
Section: Structural Changes In Proteins: a Strategy To Enhance Their mentioning
confidence: 99%
“…Achieving an increase in encapsulation efficiency from 82.6% to 94.8% in the case of soybeans and from 79.7% to 99.5% in the case of sunflower seed proteins treated by acylation. They concluded that the structural modification of these proteins increased the affinity between the active ingredient and the coating material, improving the encapsulation process, the hydration and the net charge of the protein (Nedovic and Willaert, 2013;Zhang, Tan, Abbas et al, 2014;Carbonaro et al, 2014;Teng et al, 2015).…”
Section: Cationization Reactionmentioning
confidence: 99%